2016
DOI: 10.1128/jcm.01195-16
|View full text |Cite
|
Sign up to set email alerts
|

Disk Diffusion Testing for Detection of Methicillin-Resistant Staphylococci: Does Moxalactam Improve upon Cefoxitin?

Abstract: dDisk diffusion testing is widely used to detect methicillin resistance in staphylococci, and cefoxitin is currently considered the best marker for mecA-mediated methicillin resistance. In low-inoculum diffusion testing (colony suspension at 10 6 CFU/ml), the addition of moxalactam in combination with cefoxitin has been reported to improve on cefoxitin alone for the detection of methicillin-heteroresistant staphylococci. However, moxalactam is absent from EUCAST and CLSI guidelines, which use highinoculum diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…High specificity shown by CFD and oxacillin MIC was due to the presence of inducers such as cefoxitin and NaCl which increase the identification of resistance. Cefoxitin antibiotic is found to be the best inducer for PBP2a, PBP3, and PBP4 proteins [26]. The other two phenotypic methods in this study showed a low reliability, where OSA test could detect MRSA only in 18 mecA-positive S. aureus, and showed false positive for 15 non-mecA S. aureus, whereas oxacillin disk diffusion test detected MRSA in 18 mecA-positive S. aureus and showed a false positive for 14 non-mecA S. aureus.…”
Section: Discussionmentioning
confidence: 97%
“…High specificity shown by CFD and oxacillin MIC was due to the presence of inducers such as cefoxitin and NaCl which increase the identification of resistance. Cefoxitin antibiotic is found to be the best inducer for PBP2a, PBP3, and PBP4 proteins [26]. The other two phenotypic methods in this study showed a low reliability, where OSA test could detect MRSA only in 18 mecA-positive S. aureus, and showed false positive for 15 non-mecA S. aureus, whereas oxacillin disk diffusion test detected MRSA in 18 mecA-positive S. aureus and showed a false positive for 14 non-mecA S. aureus.…”
Section: Discussionmentioning
confidence: 97%
“…Detection of methicillin resistance by S. aureus was carried out by disk-diffusion (Kirby-Bauer) technique [13,14] with 30 µg cefoxitin (Liofilchem, Roseto degli Abruzzi, Italy) according to the Clinical Laboratory Standard Institute (CLSI) guidelines [15].…”
Section: Detection Of Methicillin Resistance and Antibiotic Susceptibmentioning
confidence: 99%
“…The antimicrobial susceptibility testing of S. aureus isolates to antibiotics was carried out by disk diffusion (Kirby-Bauer) [13,14] according to the CLSI guidelines [15]. Multi discs with nine (9, including cefoxitin) antimicrobial agents (Himedia Laboratories, Mumbai India) were used, namely: penicillin G -1 i.u.…”
Section: Antibiotic Susceptibility Testing For Mrsamentioning
confidence: 99%
“…The previous use of antimicrobials, usually broad-spectrum, increases hospital costs and drives the emergence of resistant microorganisms, as it exerts a selective pressure in the ICU environment, selecting MDR isolates. It is also associated with death as a consequence of inadequate therapy [ 35 , 36 ]. Thus, we can observe the occurrence of a cycle, as MDR microorganisms from neonatal infections are deposited on surfaces exposed to air or directly by the hands of health professionals.…”
Section: Discussionmentioning
confidence: 99%